Secondary Metabolite Content and Antioxidant Activity of Ethanol Extract of Tali Putri (Cuscuta australis) at Different Heights Places - Rangga Arnelio; Aprizal Zainal; Benni Satria (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Cuscuta australis (commonly known as Tali Putri) is a parasitic weed that extracts water, minerals, and nutrients from its host plants to sustain its life cycle. Among its shared hosts, Asystasia gangetica (Israel grass) is highly susceptible due to its soft stem structure, which facilitates haustorial penetration and efficient nutrient transfer. Although generally regarded as a harmful weed, C. australis has demonstrated pharmacological potential owing to its secondary metabolites and antioxidant properties, both of which are relevant in disease treatment. This study investigated the effect of altitude on the phytochemical profile, antioxidant activity, moisture content, and ash content of C. australis and its host plant. A survey method was applied across three altitudinal zones (lowland, midland, and highland) with seven replications per site. Laboratory analyses were performed at the Plant Physiology Laboratory, Faculty of Agriculture, Andalas University, and the Higher Education Service Institution (LLDIKTI) Laboratory. Data were analyzed using analysis of variance (ANOVA) with the F-test, and significant differences (p < 0.05) were further evaluated using Duncan's New Multiple Range Test (DNMRT). The results showed that C. australis grown at high altitude exhibited the highest antioxidant activity (173.35 µg/ml), moisture content (9.06%), and ash content (5.16%). Similarly, A. gangetica collected from highland sites demonstrated superior antioxidant activity (64.39 µg/ml), moisture content (8.82%), and ash content (7.07%). By contrast, altitude had no detectable effect on the phytochemical composition of either species, both of which consistently contained flavonoids, alkaloids, phenolics, terpenoids, and triterpenoids. These findings indicate that highland populations of C. australis and A. gangetica possess enhanced bioactive properties, suggesting that high-altitude habitats may provide the most suitable raw material sources for pharmaceutical applications.